The Effect of Pregnancy Exercises on Sleep Quality among Pregnant Women - Sri Wahyuni; Nila Widya Keswara (KHD Production, 2026)
Pregnant women commonly experience sleep disturbances, which may affect maternal well-being. Prenatal exercise is a non-pharmacological intervention that can improve sleep quality by promoting relaxation and reducing physical discomfort. This study aimed to examine the effect of prenatal exercise on sleep quality among pregnant women. A quasi-experimental study with a one-group pre-test and post-test design was conducted from May to August 2024. A total of 33 pregnant women were selected using purposive sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after participation in a structured prenatal exercise program conducted regularly. Data were analyzed using a paired sample t-test. The mean PSQI score decreased significantly from 12.39 before the intervention to 5.44 after the intervention, with a p-value of 0.000, indicating a substantial improvement in sleep quality. Prenatal exercise has a significant positive effect on sleep quality in pregnant women. It can be recommended as a safe and effective intervention to be integrated into routine antenatal care services.